Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1983
DOI: 10.1111/j.1399-3054.1983.tb00741.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of light on phosphoenol pyravate carboxylase in sorghum leaves

Abstract: Upon greening of sorghum leaves (Sorghum vulgare Pers. cv. INRA 450) under white light illumination, phosphoenolpyruvate carboxylase activity increases. 17 times; at the same time, a new isoform of the enzyme appears. The aim of the present work has been to identify the process responsible for the appearance of this isoform. Greening. of the leaves in the presence of D2O did not lead to a significant increase in the buoyant density of the enzyme. On the other hand, cycloheximide was a powerful inhibitor of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…activity was paralleled by the accumulation of large amounts of PEPC in the leaf (3,9,11,17,28). These results were further extended by Sims and Hague (8,21) who observed a photoinduced increase in translatable mRNA upon greening of maize leaf, and then by Harpster and Taylor (10) who quantitatively characterized the specific mRNA in maize leaf extracts.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…activity was paralleled by the accumulation of large amounts of PEPC in the leaf (3,9,11,17,28). These results were further extended by Sims and Hague (8,21) who observed a photoinduced increase in translatable mRNA upon greening of maize leaf, and then by Harpster and Taylor (10) who quantitatively characterized the specific mRNA in maize leaf extracts.…”
supporting
confidence: 61%
“…The E-PEPC is present in etiolated leaves and displays functional and regulatory properties similar to C3-type PEPC. The G-PEPC is a C4 photosynthetic type ofPEPC which is present in green leaves and possesses specific functional, chromatographic, physicochemical, and immunochemical properties (25,28,29). The use of monoclonal antibodies specific for the G-PEPC showed that it was the lightactivated isozyme and that no conversion mechanism was responsible for the observed polymorphism (23).…”
mentioning
confidence: 99%
“…For AGPase detection, an antibody raised against recombinant potato AGPase (Tiessen et al, 2002) was used. The PEPCase antibody was raised against the purified sorghum (Sorghum vulgare) enzyme (Vidal et al, 1983). The GWD antibody was raised against the purified protein from potato (Ritte et al, 2000a).…”
Section: Antibodiesmentioning
confidence: 99%
“…Vidal and Gadal (18) and Vidal et al (19) found that two isoforms of PEPC' were present in etiolated leaves of sorghum. One form, found in the eitolated leaves, was designated E-PEPC.…”
Section: Introductionmentioning
confidence: 99%
“…Sucrose synthesis is apparently the only physiological function ofsucrose-P synthase, with the equilibrium constant for sucrose synthesis about 2 (1). This makes sucrose-P synthase a focal point for studying regulation of sucrose metabolism and partitioning.Vidal and Gadal (18) and Vidal et al (19) found that two isoforms of PEPC' were present in etiolated leaves of sorghum. One form, found in the eitolated leaves, was designated E-PEPC.…”
mentioning
confidence: 99%